Peran Masyarakat Rentan dalam Membangun Resiliensi Pasca Banjir - Muh. Bintang Widya Pratama; Rizqi Ahmad Muzaki; Tegar Vicho Virdyanto (Jurnal Hukum dan Sosial Politik, 2023)
The journal "The Role of vulnerable Communities in Building Post-Flood Resilience" explores the complex interactions between indigenous residents who live outside Mangli housing complexes, and housing residents in the Mangli area, the majority of whom are immigrants. Apart from that, this journal also examines the role of communities in building resilience after floods caused by the conversion of agricultural land. This research examines how indigenous people, as a social group, are vulnerable to the risk of flooding due to the impact of converting agricultural land into housing on the indigenous Mangli population. and how vulnerable populations attempt to adapt in modern society which is filled with various social, economic and cultural changes. By focusing on the dynamics of conflict that arise throughout the lives of residents, this journal also analyzes the adaptation strategies used by vulnerable residents in responding to flood and post-flood disasters.